Seller Liability Model For Consumer Losses Resulting From Online Purchases Of Electronic Goods - Desak Gde Dwi Arini; Nyoman Subamia; I Dewa Agung Ayu Maheswari (Universitas Dwijendra Press, 2026)
With the development of information and telecommunications technology, today's diversity is evident in various services, existing telecommunications facilities, and information technology products that can integrate all information media to assist human resources, supported by technological developments, making trade smooth and easily accessible to everyone. The problem in this research is how to regulate consumer legal protection in online electronic buying and selling transactions and what is the model of seller liability for consumer losses in online electronic buying and selling transactions. The research method uses normative legal research with a problem-based approach, including legislative approaches, conceptual approaches, and case approaches. It also uses descriptive and analytical analysis of legal materials. The research findings indicate that the legal protection of consumers in online electronic buying and selling transactions, which constitute the primary legal basis for electronic transactions in Indonesia, is regulated by Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE), Law Number 7 of 2014 concerning Trade, Government Regulation Number 80 of 2019 concerning the Implementation of Electronic Systems and Transactions, Minister of Trade Regulation Number 31 of 2023 concerning Electronic Commerce (PMSE), and the seller's legal liability model uses the principle of negligence. However, in line with developments, this has shifted to the application of strict liability, or absolute responsibility, especially in transactions with apparent high risks. Meanwhile, the ITE Law applies the principle of presumed liability, meaning it is based on the presumption of guilt, because the seller is in a position of error and is charged with compensating for losses as a form of responsibility.